Use of high frequency oscillatory ventilator in neonates with respiratory failure: the clinical practice in Taiwan and early multimodal outcome prediction - Yang, Mei-Chin (Sci Rep, 2020)
High-frequency oscillatory ventilation (HFOV) can be a rescue for neonates with refractory respiratory failure or an early elective therapy for preterm infants with severe respiratory distress syndrome (RDS). However, little is known about the current evolution and therapeutic limitations of HFOV. We therefore aimed to describe its use in clinical practice and predict the risk of mortality for neonates receiving HFOV. A retrospective observational study of all neonates treated with HFOV in a quaternary referral NICU between January 2007 and December 2016 was conducted. We classified these patients into five subgroups based on primary respiratory diagnoses. We performed the logistic regression and decision tree regression analyses to identify independent factors of 30-day mortality following HFOV. A total of 1125 patients who were ever supported on HFOV were enrolled, of whom 64.1% received HFOV as a rescue therapy, 27.2% received it as an elective therapy, and 8.7% received it for air leak. An average oxygenation index (OI) greater than 25 in the first 24 hours after the initiation of HFOV and patients with secondary pulmonary hypertension were found to have the greatest risk of in-hospital mortality (p < 0.0001). The overall in-hospital mortality rate was 25.8% (290/1125). Decision tree regression analysis revealed that neonates with refractory respiratory failure who had a pre-HFOV OI value higher than 20.5 and OI values higher than 21.5, 23.5 and 34 at 2 hours, 6 hours, and 12 hours after the use of HFOV, respectively, had a significantly increased risk of 30-day mortality. We identified the predictors and cutoff points of OI before and after the initiation of HFOV in neonates with respiratory failure, which can be clinically used as a reference for 30-day mortality. Further efforts are still needed to optimize the outcomes.